Varsities must fuel global demands - Abd Razak, Dzulkifli (2006)
IT was an important meeting that attracted the executive heads and vicechancellors of Commonwealth universities from more than 50 countries in Adelaide last week. The Association of Commonwealth Universities, under the theme "University Futures" , debated and discussed.the role of universities in ensuring future global responsibilities initiated the ‘Adelaide Conversation’. This is timely as universities are now faced with everincreasing demands to take on new responsibilities and obligations, a debate that can be traced back to the early 70s in Southeast Asia. Though the debate then was somewhat tuned towards economic interests, cultural and spiritual development were not neglected. The time has come to appreciate that a university is more than just an economic investment where the main objective is to raise not only the national output, but also create good citizenry by way of enhancing the capacity and capability of its human capital.